OPTIMATION OF TIME AND CATALYST/FEED RATIO IN CATALYTIC CRACKING OF WASTE PLASTICS FRACTION TO GASOLINE FRACTION USING Cr/NATURAL ZEOLITE CATALYST - Wega Trisunaryanti (Indonesian Journal of Chemistry, 2002)
Optimation of time and catalyst/feed ratio in catalytic cracking of waste plastics fraction to gasoline fraction using Cr/Natural Zeolite catalyst has been studied.The natural zeolite was calcined by using nitrogen gas at 500 oC for 5 hours. The chromium supported on to the zeolite was prepared by ion exchange methode with Cr(NO3)3.9H2O solution with chromium/zeolite concentration of 1% (w/w). The zeolite samples were then calcined  with nitrogen gas at 500 oC for 2 hours, oxidyzed with oxygen gas and reduced with hydrogen at 400 oC for 2 hours. The characterization of the zeolite catalyst by means of Si/Al ratio by UV-Vis spectroscopy, acidity with pyridine vapour adsorption and Na, Ca and Cr contents by atomic adsorption spectroscopy (AAS). The catalyst activity test was carried out in the cracking process of waste plastics fraction with boiling point range of 150 - 250 °C (consisted of C12 - C16 hydrocarbons) at 450 oC for 30 min, 60 min and 90 min, and catalyst/feed ratio 1/1, 1/2, 1/3, ¼ (w/w). The result of catalyst activity test  showed  that  the maximum number  conversion of gasoline fraction (C5-C11) is 53,27% with relatively low coke formation using 1/3 catalyst/feed ratio and the cracking time of 60 min.. This  catalyst has  Si/Al ratio = 1,21 (w/w) , acidity = 0,16 mmol/g and Na content = 0,81%, Ca content = 0,15% and Cr content 0,24%.